Business in Context: An Introduction to Business and its Environment - David Needle; Jane Burns (United Kingdom Cengage Learning EMEA, 2019)
Now in its seventh edition, Business in Context introduces students to all the aspects of modern business and its changing environment. This classic text has been fully updated and is essential reading for all introductory business courses, particularly business environment modules. The seventh edition combines the hallmark qualities of David Needle's style whilst new co-author Jane Burns brings over 20 years of industry experience.
Keywords: Business; Textbooks; Enterprise and Practice (BIN2045-N)